PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE (STUDI KASUS PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA TAHUN 2021-2023) - Hasanah, Ully; Augustin, Jeneva (Komunitas Manajemen Kompetitif, 2025)
Companies design and use tax avoidance strategies in order to pay less tax, thus generating large profits. This study aims to determine the effect of profitability and leverage on tax avoidance in LQ45 companies on the Indonesia Stock Exchange in 2021-2023. This study uses a quantitative method with secondary data. The research sample was obtained through purposive sampling with a total of 60 samples. The analysis technique used is multiple linear regression analysis. The results of the study show: (1) Profitability has no effect on tax avoidance with a significance value of 0.983 > 0.05 and a t-value of -0.021 < t-table 2.00247, where companies with high profitability tend to focus more on company growth and stability and avoid tax avoidance practices that can pose risks. (2) Leverage has a negative effect on tax avoidance with a significance value of 0.006 < 0.05 and a calculated t value of -2.885 < ttable 2.00247, where companies with high leverage levels mean that the company's financing is high in debt and can also result in high interest costs, thereby reducing profit before tax and can reduce tax costs without the need to carry out aggressive tax avoidance practices. (3) Profitability and leverage simultaneously have an effect on tax avoidance with a significance value of 0.009 < 0.05 and a calculated F value of 5.174 > Ftable 3.16, where profitability and leverage affect companies in making tax strategy decisions. Keywords: Taxes, Profitability, Leverage, Tax Avoidance, and LQ45 Companies